2009
DOI: 10.1021/ja904565j
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of 4f vs5fMetal−Metal Bonds in (CpSiMe3)3M−ECp* (M = Nd, U; E = Al, Ga; Cp* = C5Me5): Synthesis, Thermodynamics, Magnetism, and Electronic Structure

Abstract: Reaction of (CpSiMe(3))(3)U or (CpSiMe(3))(3)Nd with (Cp*Al)(4) or Cp*Ga (Cp* = C(5)Me(5)) afforded the isostructural complexes (CpSiMe(3))(3)M-ECp* (M = U, E = Al (1); M = U, E = Ga (2); M = Nd, E = Al (3); M = Nd, E = Ga (4)). In the case of 1 and 2 the complexes were isolated in 39 and 90% yields, respectively, as crystalline solids and were characterized by single-crystal X-ray diffraction, variable-temperature (1)H NMR spectroscopy, elemental analysis, variable-temperature magnetic susceptibility, and UV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
119
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 137 publications
6
119
1
Order By: Relevance
“…[27] Computations on [b] [25] 3.246 [b] [25] 2 Nd Cp*Al [a] C 5 H 4 SiMe 3 7.4 [b] [26] 3.220 [b] [ www.chemeurj.org a simple H 3 U À AlH model indicated that the potential energy (PE) wells for the U À Al bond are quite broad, and that each U À Al bond may vary by AE 0.2 with as little as 1 kcal mol À1 of added energy. [26] If this predicted behavior extends to the real Cp-substituted system then, taken together with the structural results, these findings suggest that the U À Al bond is easily perturbed, or "elastic".…”
Section: Assessing the Effect Of Crystal Packing Forcesmentioning
confidence: 80%
See 3 more Smart Citations
“…[27] Computations on [b] [25] 3.246 [b] [25] 2 Nd Cp*Al [a] C 5 H 4 SiMe 3 7.4 [b] [26] 3.220 [b] [ www.chemeurj.org a simple H 3 U À AlH model indicated that the potential energy (PE) wells for the U À Al bond are quite broad, and that each U À Al bond may vary by AE 0.2 with as little as 1 kcal mol À1 of added energy. [26] If this predicted behavior extends to the real Cp-substituted system then, taken together with the structural results, these findings suggest that the U À Al bond is easily perturbed, or "elastic".…”
Section: Assessing the Effect Of Crystal Packing Forcesmentioning
confidence: 80%
“…[26] As discussed earlier, within 1.0 kcal mol À1 there could be AE 0.2 of variation in the UÀAl bond lengths in [(CpSiMe 3 ) 3 UA C H T U N G T R E N N U N G (AlCp*)]. This prediction suggests that making judgments regarding electronic structure or bond strength in the three related systems with M À Ga bonds would be a risky endeavor.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Although the first structurally characterized lanthanide-transition metal bonds were reported in the early 1990s, ([(MeCN)3YbFe(CO)4]2·MeCN)∞ (Deng and Shore, 1991) and Cp2Lu(THF)-RuCp(CO)2 (Beletskaya et al, 1993), the field started developing at a fast pace only in the last decade Butovskii et al, 2010;Liddle and Mills, 2009;Minasian et al, 2009;Oelkers et al, 2012), spurred by Kempe's report of [O(SiMe2N-2-C5H3N-4-Me)2]2NdRh( 2 -C2H4) and…”
mentioning
confidence: 99%